THE IMPACT OF SOCIAL MEDIA ON VOCABULARY ACQUISITION AMONG EFL LEARNERS (Journal of Universal Science Research, 2025)
The rapid expansion of social media platforms has significantly changed how learners interact with the English language. For English as a Foreign Language (EFL) learners, social media provides authentic input, opportunities for interaction, and exposure to diverse vocabulary in real-life contexts. This paper investigates the impact of social media on vocabulary acquisition, examining both its positive contributions and potential drawbacks. The study is based on a mixed-methods approach, combining a survey of 120 EFL students with classroom observations.